Riya Dalam Selfie Di Media Sosial - Muhammad Hasnan Nahar dan Miftah Khilmi Hidayatulloh (Institut Agama Islam Negeri Padangsidimpuan, 2020)
In this recent years, social media has become a primary need for many people. Commenting on other people's statements, making complaints, finding old friends and uploading selfies exemplifies the activities in social media. From those, selfie uploaded is the most commonly done by society. According to Alfred Schuts phenomenological approach, there are two motives behind someone take selfie which are first, “in order to motive”. Someone intend to being famous and get more compliments/praise. The second one is “because motive”, someone would feel the peace/calm and satisfaction when taking a selfie and uploading it otherwise they would feel anxiety by not doing it. Regarding that motives, selfie could be transfrom as riya activity/deeds, because selfies are accompanied by the desire to get praise from human beings or something else, without wanting the pleasure of Allah SWT. The act of riya in a selfie can be prevented by avoiding areas that may appear riya deeds in it namely the area of worship, charity and clothing activities, based on the hadith of Imam Muslim number 3527, that riya can be found in worship and muamalah cases.